Mengembangkan UMKM Desa Keresek Melalui Pemasaran Digital Di Masa Pandemi Covid-19 - Iis Zilfah Adnan; Lulu Afiani; Riesal Allawiyah; Kharisma Shanov; Siti Nendah Sulaeman; Ai Pina Wahyuni (Universitas Garut, 2022)
Abstract Knowledge of digital marketing and the ability to market products through digital-based media is very necessary given the regulations on social restrictions issued by the government. Today's technology continues to grow and the benefits of using the internet are felt for the users. Some people feel dependent on the existence of the internet, including the activities of Micro, Small and Medium Enterprises (SMEs) in utilizing information technology to run their business, especially in the era of the ASEAN Economic Community (AEC). With an understanding of using digital media to market products (Digital Marketing) it will make it easier for Micro, Small and Medium Enterprises (MSMEs) to do marketing easily. Garut University KKN students are encouraged to market Tiktuk Gatra through social media, one of which is Instagram, Facebook, YouTube, and WhatsApp. The type of research carried out is qualitative and uses descriptive methods, where the author will describe or describe as a whole what is obtained in the field and what is obtained from scientific journals. The results obtained from the research carried out are the condition of the community that is still minimal in marketing through online media, there are still many people who are not obedient to the health protocol, KKN students help to market MSMEs through social media, KKN students get a positive response from micro and small business actors and from consumers who are interested in the advertisements that are made. Keywords: Covid-19; digital; pemasaran; UMKM.Â Abstrak Pengetahuan tentang digital marketing dan kemampuan memasarkan produk melalui media berbasis digital sangat diperlukan mengingat adanya peraturan tentang pembatasan sosial yang dikeluarkan oleh pemerintah. Teknologi saat ini terus berkembang dan manfaat penggunaan internet terasa bagi para pemakainya. Beberapa orang merasa ketergantungan dengan adanya internet, termasuk aktivitas Usaha Mikro Kecil dan Menengah (UKM) dalam memanfaatkan teknologi informasi untuk menjalankan usahanya khususnya pada era Masyarakat Ekonomi ASEAN (MEA). Tujuan dari pengabdian ini adanya pemahaman menggunakan media digital untuk memasarkan produk (Digital Marketing) akan memudahkan pelaku Usaha Mikro Kecil dan Menengah (UMKM) dalam melakukan pemasaran dengan mudah. Mahasiswa KKN Universitas Garut terdorong untuk memasarkan tiktuk gatra melalui media sosial salah satunya, instagram, facebook, youtube, dan wa. Jenis pengabdian yang di lakukan adalah kualitatif dan menggunakan metode deskriptif, di mana penulis akan mendeskripsikan atau menjabarkan secara keseluruhan apa yang di dapatkan di lapangan dan apa yang di dapat dari jurnal ilmiah. Hasil yang didapatkan dari pengabdian ini adalah kondisi masyarkat yang masih minim akan pemasaran melalui media online, masih banyak masyarakat yang kurang patuh terhadap protocol kessehatan, mahasiswa KKN membantu untuk memasarkan UMKM melalui social media, mahasiswa KKN mendapat respons positif dari Pelaku usaha mikrokecil dan dari konsumen yang tertarik atas iklan yang di buat.Kata-kata kunci: Covid-19; digital; marketing; UMKM.